Underpricing of initial public offerings in Singapore. - Lee, Wah Seng. (2009)
This paper analyses the pricing performance of initial public offerings (IPO) by companies which sought a listing on the Stock Exchange of Singapore (SES) Main Board and Stock Exchange of Singapore Dealers Automated Quotation (SESDAQ) during the period Jan 1987 to Jun 1994, inclusive. We find that IPOs issued during this period are generally underpriced, although there is no significant difference in the underpricing of IPOs issued between the Main Board and SESDAQ. In addition, it is found that the amount of underpricing has a general positive correlation with the times of oversubscription and size of the IPO issue. However, the results also show that the issue P/E ratio does not have any direct influence on the amount of underpricing. It is also found that the amount of underpricing is greater for local underwriter banks as compared to foreign underwriter banks. However, there is no observed trend on the amount of underpricing for each year between 1987 to 1994, except that the amount of underpricing at the 1st and 90th trading days seems to have a downward trend from 1992 to 1994.